Differing Virulence of Healthy Skin Commensals in Mouse Models of Infection - Myles, Ian A.; Moore, Ian N.; Castillo, Carlo R.; Datta, Sandip K. (Frontiers in Cellular and Infection Microbiology, 2019)
Introduction: As therapies for atopic dermatitis (AD) based on live biotherapeutic products (LBP) are developed, the potential displacement of biotherapeutic strains, and species to mucosal sites where they are not naturally found is of investigative interest. However, formal assessment of the toxicity potential of healthy skin commensal organisms has not been reported in the literature. Our previous research indicates that topical application of live Roseomonas mucosa to treat AD was associated with clinical benefit on the skin, but the effects of exposure via inhalation, eye inoculation, and ingestion were unknown. Methods: Herein we report our findings from mice inoculated with commensal strains of R. mucosa, coagulase negative Staphylococci (CNS), and Pseudomonas aeruginosa. Bacterial isolates were collected under clinical trial NCT03018275, however these results do not represent an interventional clinical trial. Results: Our tested R. mucosa isolates did not display significant infection or inflammation. However, neutropenic mice inoculated with CNS had infection without major inflammation in pulmonary models. In contrast, systemic infection generated hepatic and splenic pathology for P. aeruginosa and CNS, which was worsened by the presence of neutropenia. Discussion: Our results suggest that LBP derived from bacteria without significant infectivity histories, such as R. mucosa, may represent safer options than known pathobionts like P. aeruginosa and Staphylococcus spp. Overall, these results suggest that topically applied LBP from select skin commensals are likely to present safe therapeutic options and reinforce our prior clinical findings.